Preventing early leaving in VET: distributed pedagogical leadership in characterising five types of successful organisations - Jäppinen, Aini-Kristiina [Verfasser] (My University, 2010)
"This paper presents 14 organisers of upper secondary education in Finland with exceptionally low dropout rates. As a case study in which common strengths were defined, five types of organisations with typical characteristics were found: Working life-oriented, Networked and team-based, Cosy and traditional, Guidance-oriented, and Innovative. Distributed pedagogical leadership (DPL) was created as the theoretical basis from which organisational actions were examined. DPL implies that responsibility for students' learning is shared by the whole personnel, through long-term and systematic pedagogical practices. For this purpose, the management and leadership, curriculum, strategies, development work, study contents, and guidance were investigated through questionnaires, interviews, and documents. The phenomena were categorised and analysed multi-methodically and rated on four quality levels. As a result, a number of strengths and five organisation types were defined." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); P 2.1.1 Ohne Schulabschluss; S 5.1 Bildungsmanagement; L 1.3 Curriculumentwicklung; I 2.2.1 Westeuropa; Ausbildungsabbruch; Schulabbrecher; Bildungsmanagement; Curriculumentwicklung; Berufsorientierung; Finnland